Cooperating with the State: Evidence from Survey Experiments on Policing*. Issue 2 (10th November 2016) - Buckley, Noah; Frye, Timothy; Gehlbach, Scott; McCarthy, Lauren A.
Abstract: We examine cooperation with the state using a series of survey experiments on policing conducted in late 2011 in Moscow, Russia, where distrust of the state is high and attempts to reform the police have been ineffective. Through various vignettes that place respondents in situations in which they are the witness or victim of a crime, we experimentally manipulate crime severity, identity of the perpetrator (whether the crime is committed by a police officer), monetary rewards, appeals to civic duty, and the opportunity cost of time spent reporting. Of these factors, crime severity and identity of the perpetrator are robustly associated with a propensity to report. Our research design and results contribute to a large literature on cooperation with the state by examining variables that may be more salient or function differently in countries with weak institutions than in developed democracies.